Improving the Ability to Understand the Quran Reading through the Application of the Mind Map Method during the Covid 19 Pandemic in Al-Qur'an Education Institutions Qurrota A'yun at Kutaraja Village, Maleber District, Kuningan Regency - Saepudin, Saepudin; Kartika, Ika; Suhada, Ahmad; Ahyudin, Didin; Agustianty, Efit Fitria; Arjadisastra, Nasihin; Hidayat, Rohman (Budapest International Research and Critics University, 2021)
The Qur'an house